STRATEGI GURU PENDIDIKAN AGAMA ISLAM TERHADAP PEMBINAAN KARAKTER DI SMAN 10 MAKASSAR - Rachmawati, Aliyya Rose; Mustamin; Raehana, Syarifa; Wahab, Abdul; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the strategies of Islamic Religious Education (PAI) teachers in developing the character of tenth-grade students at SMA Negeri 10 Makassar, the forms of character development implementation, and the supporting and inhibiting factors influencing the process. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects consisted of PAI teachers and tenth-grade students selected using purposive sampling techniques. Data analysis was carried out through data collection, data reduction, data display, and conclusion drawing with verification using triangulation techniques. The results show that the strategies implemented by PAI teachers in character development include giving advice, instilling discipline, and habituating religious activities. The implementation of character development is carried out holistically through intracurricular and extracurricular activities, habituation programs, religious activities, enforcement of school rules, teacher role modeling, and collaboration between schools and parents. Supporting factors include family involvement, teacher competence, a conducive school environment, and student motivation, while inhibiting factors include low self-control among students, the influence of social environments and media, and limited learning media. In conclusion, character development can be effectively achieved through the synergy of teachers, schools, families, and the environment, supported by appropriate and innovative teaching strategies.